Mixtures of oppositely charged polypeptides as high-performance dispersing agents for single-wall carbon nanotubes. - Lee, G; Sach, C; Green, M; Wong, L; Salzmann, C (2010)
A new and simple strategy for the dispersion of single-wall carbon nanotubes in aqueous media is presented which does not rely on hydrophobic interactions between the polypeptidic dispersing agent and the nanotubes, and allows the surface charge of the resulting conjugate materials to be controlled.